Baby city - McFadden, Freida ([Place of publication not identified] : [Freida McFadden & Kelly Stoddard], 2015)
There are only three things in this world that are certain: death, taxes, and babies. Nobody knows this truth better than Emily McCoy, a third year resident working in Baby City, the affectionate nickname for the busy Labor and Delivery unit at a New York City hospital. On a typical day in Baby City, Emily delivers more babies than the number of hours of sleep she manages to squeeze in that night. And definitely more than the number of dates she's been on since she started her training in OB/GYN two years earlier. As Emily works tirelessly to safely herald baby after baby after baby (after baby) into the world, she becomes well acquainted with the three hard facts of Baby City:1) Babies never come when you want them to .2) Babies always come when you don't want them to. 3) You don't know who your true friends are until your baby is sliding down the birth canal.
Keywords: Residents (Medicine) -- Fiction; Gynecologists -- Fiction; Obstetricians -- Fiction; Childbirth -- Fiction; Delivery (Obstetrics) -- Fiction; Pregnancy -- Fiction; Newborn infants -- Fiction